Chain elongation process for caproate production using lactate as electron donor in Megasphaera hexanoica. (February 2022) - Kang, Seongcheol; Kim, Hyunjin; Jeon, Byoung Seung; Choi, Okkyoung; Sang, Byoung-In
Graphical abstract: Highlights: First report about lactate-using chain elongation in Megasphaera hexanoica . Characteristic using lactate as electron donor was evaluated compare to fructose as electron donor. Caproate production was enhanced when using fructose and lactate simultaneously. Comprehensive interpretation about chain elongation process using lactate in M. hexanoica was proposed. Abstract: Megasphaera hexnaoica is anaerobic bacteria who has well running reverse β-oxidation pathway. In previous study, the strain showed excellent production of medium chain carboxylic acids (MCCAs) using fructose as electron donor. In this study, chain elongation process study using lactate instead of fructose was conducted in M. hexnaoica fermentation. It was found that M. hexanoica can use lactate as electron donor in chain elongation process. 8.9 g/L caproate production was achieved in fermentation using lactate as sole electron donor. Compare to fructose condition, lactate as electron donor showed more than 3 times higher specific titer and specific productivity. In addition, when fructose and lactate were used as electron donor simultaneously, further improvement of MCCAs production was observed to achieve maximum caproate productivity of 20.9 g/L/day. Utilization of lactate as electron donor in M. hexanoica showed potential opportunity in chain elongation process.